Роман А. Любки "Твій погляд, Чіо-Чіо-Сан": кримінальний сюжет крізь оптику сценічного дійства - Насмінчук, Г.Й. (Слово і Час, 2019)
У статті проаналізовано музичне начало як значущий компонент поетики роману “Твій
погляд, Чіо-Чіо-Сан” (ідеться про змістовий, структурний та семантичний рівні). Доведено, що
контамінування, співдія вербального й музичного творів психологізують та індивідуалізують
образну систему, поглиблюють актуальну проблематику, інтелектуалізують авторську нарацію.
Інкорпорація сценічного твору у вербальний текст сприяє розкодуванню прихованих сенсів. Стиль
роману А. Любки окреслено як такий, що тяжіє до традиції, відбиває вплив постмодерністської
естетики. The paper deals with the literary style characteristics of the novel “Your Look, Chio-Chio-san” by
A. Liubka. The researcher analyzes the presence of the musical element as a significant component
of the novel’s poetics on the levels of sense, structure and semantics. The events of the novel unfold
in an intertextual dialogue with Giacomo Puccini’s opera “Madama Butterfl y”, so that the content of
the opera becomes an active component in creating meanings. The connection with the musical text
allows tracing the variability of the literary textual content both on the literal and conceptual levels. The
opera affects the narrator with greater force than his living communication with the people around.
Insertions from the opera, bringing some chaos in the orderly verbal text, at the same time clarify a
number of aspects hidden behind the scenes of ideological, plot and imaginative cause-and-eff ect structure. While the first part of the novel, which records the fact of a young woman’s death and shows
everything as unambiguous and understandable, looks like a forensic documentary, the final section
seems to be a puzzle of hints and allusive assumptions. Moreover, the author is in no hurry to decode
the text; this must be done by the recipient, drawn into the game of looking for hidden meanings. It is
proved that the co-operation of different semiotic levels within the limits of one text and combination
of verbal and musical works contribute to psychologizing and individualizing images, deepening the
actual problems and intellectualizing the author’s narration. Incorporation of the stage work into the
verbal text impacts on the decoding of hidden meanings. The analysis of the novel allows the researcher
to assert that the style of A. Liubka is being formed under the influence of postmodern aesthetics.